Use of water-soluble phosphine ligands in heterogeneous hydroformylation catalysis : application to long-chain 1-alkenes - Du Toit, Judith G O (Department of Chemistry, 2016)
The two-phase rhodium-tri(m-sulfonatophenyl)phosphine (Rh-TPPTS) system for the hydroformylation of 1-octene, 1-decene, and 1-dodecene to the corresponding aldehydes, has been investigated. Due to the two distinct phases - the catalytic species in the aqueous phase and the products and reactants in the organic phase - the separation of the catalyst was easily facilitated. A comparison was made of the activity, selectivity towards linear aldehydes, and catalyst lifetime of two systems where i) the active catalytic species were generated in situ from rhodium trichloride (RhCl₃.3H₂O) and excess phosphine ligand (TPPTS) under mild hydroformylation conditions (5 MPa H₂/CO (1:1); 100 °C); and ii) where the rhodium(I) complex, RhH(CO)(TPPTS)₃ is used as the catalyst precursor. The former system was found to be superior in activity and selectivity to that of the latter, achieving fairly high conversions of ca. 60% for the hydroformylation of 1-octene, with n:iso ratios of up to 16:1 for a catalyst composition a Rh:P ratio of 1:30. Unfortunately low conversions of ca. 10% for the hydroformylation of 1-decene and ca. 4% for that of 1-dodecene resulted under the same conditions. While the reasons for the drastic decrease in conversion for C₁₀ and C₁₂ alkenes is not completely clear, this poor conversion is attributed to the extremely low solubility of the long-chain 1-alkenes in the aqueous phase. Under certain optimum conditions (Rh:P ≥ l :20), virtually no leeching of rhodium into the organic phase was detected. A ³¹P NMR spectroscopic study was undertaken in an attempt to ascertain the nature and distribution of rhodium tertiary-phosphine complexes in the aqueous phase before and after the mixture was subjected to standard hydroformylation conditions.